Parametric Study on Effects of Water-Cement Ratio to Compressive Strength of RHA Mortar - Anwar, Adilhakimin (Universiti Teknologi Petronas, 2011)
The main objective of this research is to investigate the effects of using Rice Husk Ash (RHA) as a partial cement replacement material in mortar mixes. Water to cement ratio (w/c) were varied namely 0.50 and 0.55 while RHA content were differed from 0% to 45% at increment of 5%. The studied binder:sand ratio (b:s) was varied at 1:3 and 1:4. Compressive strengths of the mixes were determined at 7, 28 and 60 days. In addition, the water absorption and initial water suction rate of mix samples were also investigated. The obtained results show that most of the mortar mixes up to 20% of RHA replacement level achieved higher strength compared to other mixes with RHA replacement level exceeding of 20%. Furthermore, this study showed that mixes with w/c of 0.55 possesses higher strength.